Peningkatan Kepuasan Kerja Guru PNS SMP Negeri XYZ di Kota Karawang Melalui Lingkungan Kerja Fisik dan Motivasi Kerja - Rukpawanda, Sri Ajeng; Lestari, Dian (Universitas Batanghari, 2024)
The decrease in absenteeism for civil servant teachers at state middle school. Reducing the level of teacher absenteeism can provide benefits especially for all students in pursuing education. The aim of this research in to investigate eforts to increase teacher job satisfaction ehich focuses on aspects of physical work environvement and work motivation. This research employs quantitative research methods involving 32 participants selected through a sampling technique known as saturation sampling, the data collection techniques used are literature study and field research. Data analysis was carried out by interoreting the calculation result table using SPSS version 26 from previously processed data. The result of this research show that simultaneously the physical work environment and work motivation have an influence on the job satisfaction of civil servant teachers at XYZ State Middle School in the city of Karawang.